2007
DOI: 10.1186/1471-2164-8-467
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chromosomal alpha-proteobacterial small RNAs by comparative genome analysis and detection in Sinorhizobium meliloti strain 1021

Abstract: Background: Small untranslated RNAs (sRNAs) seem to be far more abundant than previously believed. The number of sRNAs confirmed in E. coli through various approaches is above 70, with several hundred more sRNA candidate genes under biological validation. Although the total number of sRNAs in any one species is still unclear, their importance in cellular processes has been established. However, unlike protein genes, no simple feature enables the prediction of the location of the corresponding sequences in geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 80 publications
3
65
0
4
Order By: Relevance
“…The same pattern of induction was observed in strain Smbl503 (complemented hfq mutant) (data not shown). Further experiments will be required to elucidate whether S. meliloti Hfq auto-controls its own expression at a translational level, as described for E. coli (65). The greater expression level of hfq during stationary phase suggests that Hfq plays a role in the stationary phase adaptation and may account, at least in part, for the lower cell density reached by the mutant than by the parental strain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same pattern of induction was observed in strain Smbl503 (complemented hfq mutant) (data not shown). Further experiments will be required to elucidate whether S. meliloti Hfq auto-controls its own expression at a translational level, as described for E. coli (65). The greater expression level of hfq during stationary phase suggests that Hfq plays a role in the stationary phase adaptation and may account, at least in part, for the lower cell density reached by the mutant than by the parental strain.…”
Section: Resultsmentioning
confidence: 99%
“…Such a regulatory strategy would allow the bacteria to react quickly and at lower energetic cost to the stresses and sudden variations in their environments that they experience during the establishment of the symbiosis (39); as recently reviewed by Waters and Storz (69), sRNA-mediated regulation has several advantages compared to protein-regulated regulation during stress responses. Recent comparative genome analysis and prediction studies have suggested the existence of a number of sRNAs in S. meliloti, and some have been experimentally verified (11,65,68), but their regulatory roles in bacterial physiology and symbiosis has not yet been investigated. Expression of several of these predicted sRNAs in S. meliloti has been confirmed by Northern blots and microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, comparative genomics-based predictions have become a standard method to search for ncRNA genes conserved in at least two bacterial genomes (10,53,100,163,210,303,309). Thus, the high number of genome sequences from marine picocyanobacteria provides an excellent data set for the computational prediction of ncRNA genes.…”
Section: Two-component Systems and Crp-type Regulatorsmentioning
confidence: 99%
“…The mass spectrometric analysis of the samples was performed with an Orbitrap Velos Pro mass spectrometer (Thermo Scientific, Germany). An Ultimate nanoscale rapid-separation LC-high-pressure liquid chromatography (nanoRSLC-HPLC) system (Thermo Scientific, Germany), equipped with a custom 20-cm by 75-m column filled with 1.7-m C 18 beads, was connected on line to the mass spectrometer through a Thermo Scientific Nanospray Flex ion source. One microliter of the tryptic digest was injected onto a C 18 micro-preconcentration column (300 m [inner diameter] by 5 mm).…”
Section: Methodsmentioning
confidence: 99%
“…meliloti has been shown to express more than 400 different sRNAs under different growth conditions and lifestyles, i.e., both free-living in the soil and symbiotically associated in a plant (15)(16)(17)(18)(19)(20)(21). In addition, S. meliloti expresses a functional homolog of the Escherichia coli Hfq protein, a chaperone of RNA-RNA interactions and a modulator of RNA activity (22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%